AN INVESTIGATION ON THE HISTORY AND STRUCTURE OF KOREAN SHAMANISM - CHAČATRJAN, Arevik (International Journal of Korean Humanities and Social Sciences, 2016)
Korean civilization has been influenced by different religions, such as Buddhism, Taoism, Confucianism and lately Christianity. However, the nucleus of the Korean culture is Shamanism, which is a conjuring religious phenomenon. Even though Shamanism belongs to the first page in the history of religions, it has been transmitted to next generations of Korea in different forms, somewhat surviving until today. A possible reason for this may be that Shamanism exhibits a dynamic and selective tradition that has adapted to different religions around it. It may also provide human beings with the blessings that they are deprived of in today’s society. In this study, the origin and development of Shamanism in Korea, including the three dynasties of Silla, Koryo and Yi, were investigated. The primitive forms of ancient beliefs of Koreans as well as the structure of Shamanism and related rituals were described. Information was also provided on Shaman ritualists and the instruments they utilized in rituals.